Podzolization as a deferralitization process: a study of an Acrisol-Podzol sequence derived from Palaeozoic sandstones in the northern upper Amazon Basin - do Nascimento, N. R.; Bueno, G. T.; Fritsch, E.; Herbillon, A. J.; Allard, T.; Melfi, A. J.; Astolfo, R.; Boucher, H.; Li, Y. (Wiley-Blackwell, 2004)
Morphological, geochemical and mineralogical studies were carried out in a representative soil catena of the low-elevation plateaux of the upper Amazon Basin to interpret the steps and mechanisms involved in the podzolization of low-activity clay soils. The soils are derived from Palaeozoic sandstones. They consist of Hydromorphic Podzols under tree savannah in the depressions of the plateaux and predominantly of Acrisols covered by evergreen forest elsewhere.Incipient podzolization in the uppermost Acrisols is related to the formation of organic-rich A and Bhs horizons slightly depleted in fine-size particles by both mechanical particle transfer and weathering. Weathering of secondary minerals by organic acids and formation of organo-metallic complexes act simultaneously over short distances. Their vertical transfer is limited. Selective dissolution of aluminous goethite, then gibbsite and finally kaolinite favour the preferential cheluviation of first Fe and secondly Al. The relatively small amount of organo-metallic complexes produced is related to the quartzitic parent materials, and the predominance of Al over Fe in the spodic horizons is due to the importance of gibbsite in these low-activity clay soils.Morphologically well-expressed podzols occur in strongly iron-depleted topsoils of the depression. Mechanical transfer and weathering of gibbsite and kaolinite by organic acids is enhanced and leads to residual accumulation of sands. Organo-metallic complexes are translocated in strongly permeable sandy horizons and impregnate at depth the macro-voids of embedded soil and saprolite materials to form the spodic Bs and 2BCs horizons. Mechanical transfer of black particulate organic compounds devoid of metals has occurred later within the sandy horizons of the podzols. Their vertical transfer has formed well-differentiated A and Bh horizons. Their lateral removal by groundwater favours the development of an albic E horizon. In an open and waterlogged environment, the general trend is therefore towards the removal of all the metals that have initially accumulated as a response to the ferralitization process and have temporarily been sequestrated in organic complexes in previous stages of soil podzolization.